2022
DOI: 10.1177/15266028221119309
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review of Risk Assessment of Abdominal Aortic Aneurysm Rupture Based on Biomechanics-Related Morphology

Abstract: An abdominal aortic aneurysm (AAA) is a typical aortic disease with serious complications. In clinical practice, the decision to intervene in treatment depends on the rupture risk of AAA. Therefore, monitoring the progression of the disease and accurately assessing the rupture risk is of great importance for its treatment. Studies have shown that the biomechanical indicators based on multi-scale models are more effective in accurately assessing the rupture risk of AAA. However, using computational fluid dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 121 publications
(223 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that morphological metrics derived based on 3D information are more accurate and consistent than 2D manual measurement ( Ma et al, 2004 ; Ryu et al, 2011 ; Rajabzadeh-Oghaz et al, 2018 ). However, recent studies have revealed that the morphology metrics alone may not be sufficient for predicting the rupture risks of IA, especially in small unruptured IAs ( Abboud et al, 2017 ; Korja et al, 2017 ; Longo et al, 2017 ; Hu et al, 2021 ; Ren et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that morphological metrics derived based on 3D information are more accurate and consistent than 2D manual measurement ( Ma et al, 2004 ; Ryu et al, 2011 ; Rajabzadeh-Oghaz et al, 2018 ). However, recent studies have revealed that the morphology metrics alone may not be sufficient for predicting the rupture risks of IA, especially in small unruptured IAs ( Abboud et al, 2017 ; Korja et al, 2017 ; Longo et al, 2017 ; Hu et al, 2021 ; Ren et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%